Effects of feeder design (conventional dry feeder, dry shelf-feeder, and wet/dry shelf-feeder) on finishing pigs - Amornthewaphat, N.; Hancock, Joe D.; Behnke, Keith C.; McKinney, Leland J.; Starkey, C.W.; Lee, D.J.; Jones, C.L.; Park, J.S.; Dean, D.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed from wet/dry shelf-feeders had 6.8% greater ADG compared to those fed from dry shelf-feeders and used 18.3% less water than those fed from conventional feeders.
Keywords: Swine; Feeder design; Wet/Dry feeder; Finishing pigs